Analisis Kemampuan Membaca Pemahaman Siswa Ditinjau Dari Minat Baca Siswa Kelas V SD - Rima Aviana; Rien Anitra; Dina Anika Marhayani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to: 1) To describe students' reading comprehension ability in terms of high reading interest in class V SDN 82 Singkawang. 2) To describe students' reading comprehension ability in terms of moderate reading interest in class V SDN 82 Singkawang. 3) To describe students' reading comprehension ability in terms of low reading interest in class V SDN 82 Singkawang. This study uses a descriptive type and a qualitative approach. The subjects in this study were students of class V SDN 82 Singkawang, totaling 22 people. Data analysis techniques used are data reduction data, data presentation, and drawing conclusions. The results of this study indicate that students with high reading interest have poor comprehension skills, students who have reading interest while having sufficient comprehension skills, and students who have low reading interest have poor understanding abilities.